Reducing Sleep Disturbance by Using Slow Deep Breathing and Dhikr in Cancer Patients During Chemotherapy - Fahrun Nur Rosyid; Beti Kristinawati; Nurlaila Fitriani; Sugiyarti; Ahmad Fadhlur Rahman (Future Science)
This study aims to investigate the effects of slow deep breathing (SDP) and dhikr on sleep disturbance in cancer patients during chemotherapy. This study used a Quasi-experiment design. A total of 44 cancer patients experiencing chemotherapy who met the inclusion criteria were divided into 2 groups of 22 patients. The treatment group practiced SDB and dhikr, while the control group practiced normal breathing. This intervention was performed for 30 minutes and repeated for 3 cycles of chemotherapy. Furthermore, sleep disturbance is measured by the Pittsburgh Sleep Quality Index sheet. The data is analyzed using the Paired t-test, independent t-test, and Chi-square test with a significance limit of p <0.05. The result after 3 treatment cycles, sleep disturbances decreased in the treatment group from 7.64 ± 2.19 to 6.73 ± 1.78 or decreased by 0.91 ± 1.54, but in the control group, there was an increase from 5.00 ± 1 .90 to 5.18 ± 1.99 or an increase of 0.18 ± 0.85. The analysis results of SDP and dhikr effect on sleep disturbance in cancer patients during chemotherapy is significant (p=0.010). This study concludes SDB, and Dhikr can reduce sleep disturbance in cancer patients during chemotherapy.